If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -10 + -4y = 7y + -16 Reorder the terms: -10 + 8y + -4y = 7y + -16 Combine like terms: 8y + -4y = 4y -10 + 4y = 7y + -16 Reorder the terms: -10 + 4y = -16 + 7y Solving -10 + 4y = -16 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -10 + 4y + -7y = -16 + 7y + -7y Combine like terms: 4y + -7y = -3y -10 + -3y = -16 + 7y + -7y Combine like terms: 7y + -7y = 0 -10 + -3y = -16 + 0 -10 + -3y = -16 Add '10' to each side of the equation. -10 + 10 + -3y = -16 + 10 Combine like terms: -10 + 10 = 0 0 + -3y = -16 + 10 -3y = -16 + 10 Combine like terms: -16 + 10 = -6 -3y = -6 Divide each side by '-3'. y = 2 Simplifying y = 2
| 8x-6=x+8+6x | | 0.2x+0.6=4.2 | | 54-10x=20+7x | | -x^3-3x^2-7x+5=0 | | 3u-6=4u+12 | | 7xy-4(x^2)y-2xy-7x(y^2)=0 | | .6x-.3=.5x+4 | | -5(x+9)-x-4=-6(x+6)-13 | | 30k+70=20k+8 | | 16-16t^2+196=0 | | 10(v+1)-4v=3(2v+1)-6 | | 5x-1+2x=4 | | 0=x^2-18x+16 | | 2x-1+3x=4 | | 4y^2-20y+16= | | x(8-2x)(15-2x)=0 | | x=1.667x-20 | | f(x)=x^60*sin(8x) | | 0=5*2y | | 5(5p+4)= | | 12(x-7)=-3(x+2) | | 5x^4-7x^2-24=0 | | x^2-28x-2013=0 | | 3y+2*y-1= | | 4x=16-2x | | 3x-2=7x+17 | | -16t^2+48t-640=0 | | (x+4)(x-6)=7x | | 36-9a^2=0 | | -16p-5(3-4p)=2(p-4)-11 | | 4y^2-24y+20= | | 4y^2-12y-40= |